PENGARUH SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI KASUS PADA KANTOR DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KAB. MAMASA) - Carolus Askikarno Palalangan (Universitas Pendidikan Nasional, 2019)
The purpose of this research is to determine the effect of the internal control system on the quality of local government financial reports on Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Mamasa. Data collection techniques using questionnaires. The sample in this research were 32 employee of Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Mamasa. This study uses simple random sampling technique. Data were analysed using regression analysis techniques, f-test, and t-test by software SPSS for windows. The results found that there was a significant influence between the control environment, risk assessment, control activities, information and communication, and monitoring of the quality of financial statements simultaneously; partially, and there is a significant influence between the control environment, risk assessment, control activities, information and communication, and monitoring of the quality of financial statements.